2017
DOI: 10.1002/jez.2113
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acclimation temperature, salinity, and behavior on the thermal tolerance of Mozambique tilapia (Oreochromis mossambicus)

Abstract: Mozambique tilapia have been shown to be incredibly stress tolerant with respect to environmental salinity, hypoxia, and ammonia concentrations. Temperature challenges to this species have shown that they have difficulty with cold acclimation. The purpose of this study was to measure the effects of acclimation temperature and salinity on the thermal tolerance of Mozambique tilapia as assessed by critical thermal maxima (CT) and critical thermal minima (CT). We also monitored fish behavior and quantified ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…Our results suggest that fish were experiencing physiological hypoxia at water temperatures approaching CT max that led to the initiation ASR to increase oxygen delivery to the tissues. King and Sardella (2017) observed ASR during CT max trials in the Mozambique tilapia ( Oreochromis mossambicus ), and they also reported ventilation cessation behavior, which we did not observe in M. insignis or A. agassizii . King & Sardella attributed the use of ASR in the Mozambique tilapia to increased metabolic demands on the fish during acute thermal increase and hypoxemia that would occur with ventilation cessation behavior.…”
Section: Discussioncontrasting
confidence: 49%
“…Our results suggest that fish were experiencing physiological hypoxia at water temperatures approaching CT max that led to the initiation ASR to increase oxygen delivery to the tissues. King and Sardella (2017) observed ASR during CT max trials in the Mozambique tilapia ( Oreochromis mossambicus ), and they also reported ventilation cessation behavior, which we did not observe in M. insignis or A. agassizii . King & Sardella attributed the use of ASR in the Mozambique tilapia to increased metabolic demands on the fish during acute thermal increase and hypoxemia that would occur with ventilation cessation behavior.…”
Section: Discussioncontrasting
confidence: 49%
“…Therefore, Mozambique tilapia has been used in breeding to improve the saltwater and cold tolerance of other tilapias [21,26,27]. The species has also been used as a model to study environmental factors [28,29] and response to pathogens [30]. Mozambique tilapia is native to the river of South Africa [31], but its numbers have decreased due to introduction of invasive fish species, including Nile tilapia.…”
Section: Introductionmentioning
confidence: 99%
“…Research comparing the cold-tolerance characteristics among the different Nile tilapia species located in different geographic locations such as Egypt, Ghana, and the Ivory Coast revealed that Nile tilapia have survived through natural selection for many years, and the physiologies and lethal temperature ranges reflect different cold-tolerant phenotypic characteristics acquired from their ancestral populations [ 42 , 43 ]. Although it is well known that there are intraspecies phenotypic differences in temperature tolerance [ 44 , 45 , 46 , 47 ], there is still a lack of information regarding this genetic variation. The physiological basis of this study was the long-term collection of populations possessing different cold-tolerant phenotypes.…”
Section: Discussionmentioning
confidence: 99%